(untitled) (Third Sector Social Economic Review, 2025)
In today’s highly competitive landscape driven by globalization, gastronomy tourism is becoming increasingly significant for various destinations. This study aims to assess the current state of gastronomy tourism in Aksaray Province while identifying its strengths, weaknesses, opportunities, and threats through a SWOT analysis. Additionally, it offers suggestions to enhance the development of gastronomy tourism in the region. The research employed a semi-structured interview method, a qualitative approach, conducting face-to-face interviews with 15 participants, including managers, employees, tourism academicians, and other stakeholders involved in tourism enterprises operating in Aksaray. The data collected from these interviews were analyzed using SWOT analysis and content analysis methods. The findings revealed that Aksaray Province’s greatest strength in gastronomic tourism is its location in the Cappadocia region, which boasts a rich culinary culture. However, a significant weakness identified was the inadequate promotion of the region and the lack of local dishes on the menus of food and beverage establishments.